Growth of Intestinal Neomucosa on Pedicled Gastric Wall Flap, a Novel Technique in an Animal Model. Issue 6 (1st June 2022) - Sakarellos, Panagiotis; Papalois, Apostolos; Gakiopoulou, Harikleia; Zacharioudaki, Iro; Katsimpoulas, Michalis; Belia, Marina; Moris, Dimitrios; Aggelou, Kyveli; Vagios, Ilias; Davakis, Spiridon; Vailas, Michail; Liakakos, Theodoros; et al.
Abstract: Background: Short bowel syndrome (SBS) remains an unsolved issue in modern medicine. Numerous experimental surgical techniques have been proposed in the attempt to increase the intestinal absorptive capacity. Materials and Methods: Ten female Landrace pigs, divided in two groups of 5 (A and B), were explored through a midline incision. A spindle-shaped vascularized full-thickness gastric wall flap (GWF) consisting of part of the major curvature with the gastroepiploic arch preserved was de-epithelialized and then placed as a "patch" to cover an antimesenteric border defect of either a nonfunctional blind intestinal loop (group A) or a functional intestinal loop of the gastrointestinal tract (group B). A spindle-shaped curved, rigid, low density polyethylene (LDPE) splint was sutured on the external surface of the patch in order to prevent shrinkage of GWF and collapse of the intestinal wall in group A. Results: There was a decrease of both dimensions of the patch. Microscopically a thin layer of columnar epithelial cells covered the center of the patch, evolving in shorter, blunt, poorly developed villi with increasing maturation laterally. The patch surface was covered by nearly 90%. In the three animals that died prematurely the coverage of GWF was negligent or suboptimal directly dependent on the length of survival. Conclusions: The hereby-described patching technique demonstrated the growth of intestinal neomucosa on the GWF. The capability of the stomach to provide large flaps and the advantages of the use of native tissues render this animal model valuable for the future research in the field.